Cutting through the biofuel confusion: A conceptual framework to check the feasibility, viability and desirability of biofuels. (May 2021) - Ripa, M.; Cadillo-Benalcazar, J.J.; Giampietro, M.
Abstract: Biofuels represent a complex issue in the sustainability discourse as they require the simultaneous consideration of different dimensions and scales of analysis. This situation explains the co-existence of contrasting 'scientific evidence' about their performance. This paper presents a novel conceptual framework that integrates four key aspects of the performance of biofuels: (1) the social factors determining the desirability of biofuel use on the demand side – why do we want to produce biofuels?; (2) the internal technical and economic constraints affecting the viability of their mode of production on the supply side – how can we produce biofuels?; (3) the external biophysical constraints limiting the feasibility of their production – what are the material limits imposed by the availability of natural resources?; (4) the level of openness of the biofuel system referring to the imports used to overcome local limits – the level of externalization of the requirement of natural resources and technical production factors reducing energy security. The proposed framework generates a biophysical characterization of the supply function of a biofuel system (which inputs are needed to generate the supply) contextualized against a biophysical characterization of the societal demand (what inputs the society is ready to invest in the energy system in order to obtain the supply). Graphical abstract: Image 1 Highlights: Different non-equivalent framings generate a systemic confusion on biofuels. A conceptual framework grounded in energetics and relational analysis is proposed. The framework allows to assess feasibility, viability, desirability, openness.